I-CReST 2021 International Conference on Research and Practices in Science, Technology and Social Sciences: abstract book - Ibrahim, Salizatul Ilyana (Center of Foundation Studies, 2021)
I-CReST 2021’s main theme addresses four tracks to encourage scientific writing/ publication across multidisciplinary research in the broad fields of:-